Effectiveness of PARP inhibition in enhancing the radiosensitivity of 3D spheroids of head and neck squamous cell carcinoma - Zhou, Chumin; Fabbrizi, Maria Rita; Hughes, Jonathan R.; Grundy, Gabrielle J.; Parsons, Jason L. (Frontiers in Oncology, 2022)
A critical risk factor for head and neck squamous cell carcinoma (HNSCC), particularly of the oropharynx, and the response to radiotherapy is human papillomavirus (HPV) type-16/18 infection. Specifically, HPV-positive HNSCC display increased radiosensitivity and improved outcomes, which has been linked with defective signalling and repair DNA double strand breaks (DSBs). This differential response to radiotherapy has been recapitulated in vitro using cell lines, although studies utilising appropriate 3D models that are more reflective of the original tumour are scarce. Furthermore, strategies to enhance the sensitivity of relatively-radioresistant HPV-negative HNSCC to radiotherapy are still required. We have analysed the comparative response of in vitro 3D spheroid models of oropharyngeal squamous cell carcinoma to x-ray (photon) irradiation, and provide further evidence that HPV-positive cells, in this case now grown as spheroids, show greater inherent radiosensitivity compared to HPV-negative spheroids due to defective DSB repair. We subsequently analysed these and an expanded number of spheroid models, with a particular focus on relatively radioresistant HPV-negative HNSCC, for impact of poly(ADP-ribose) polymerase (PARP) inhibitors (olaparib and talazoparib) in significantly inhibiting spheroid growth in response to photons, but also proton beam therapy. We demonstrate that in general, PARP inhibition can further radiosensitise particularly HPV-negative HNSCC spheroids to photons and protons leading to significant growth suppression. The degree of enhanced radiosensitivity was observed to be dependent on the model and on the tumour site (oropharynx, larynx, salivary gland or hypopharynx) from which the cells were derived from. We also provide evidence suggesting that PARP inhibitor effectiveness relates to homologous recombination repair proficiency. Interestingly though, we observed enhanced effectiveness of talazoparib versus olaparib specifically in response to proton irradiation. However, our data generally support that PARP inhibition in combination with radiotherapy (photons and protons) should be considered further as an effective treatment for HNSCC, particularly for relatively radioresistant HPV-negative tumours.